MOTORCYCLE WASH BUSINESS TRAINING: Business Inspiration for Beginners among Teenagers - Salikin Salikin (Jurnal PKM Manajemen Bisnis, 2023)
Building a business is not as easy as turning your palm, especially for beginners. As a new person, of course you don't have a lot of knowledge, experience and expertise in running a business properly. Then the right step is to start a small-scale business. This is done as a learning medium, in order to provide a real picture of the business world. So that a business spirit is born which in the future can become a provision to build a better business. This activity was carried out to provide knowledge and reference for youth in the village of Caruban, Kebumen. The method of activity is explanation of the material, giving examples and simulations. The number of participants who took part in this activity were young children in the village of Caruban, Kebumen, with 47 people. The result of the activity was an increase in the knowledge of the participants about entrepreneurship, especially for beginners. So that the participants have references in building a business according to their capacity, for example by running a motorbike washing business. This training also provides skills provision as one of the assets in living life in the future.